2015
DOI: 10.1007/s12041-015-0528-7
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary genetic linkage map of Indian major carp, Labeo rohita (Hamilton 1822) based on microsatellite markers

Abstract: Linkage map with wide marker coverage is an essential resource for genetic improvement study for any species. Sex-averaged genetic linkage map of Labeo rohita, popularly known as 'rohu', widely cultured in the Indian subcontinent, was developed by placing 68 microsatellite markers generated by a simplified method. The parents and their F1 progeny (92 individuals) were used as segregating populations. The genetic linkage map spans a sex-averaged total length of 1462.2 cM, in 25 linkage groups. The genome length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…A 17% higher average growth rate per generation was achieved after four generations of selection (Das Mahapatra et al, 2006). Our previous studies have also reported DNA markers such as SSRs (Das et al, 2005;Patel et al, 2009;Sahu et al, 2012), SSR and SNP -based linkage maps (Robinson et al, 2014;Sahoo et al, 2015) and transcriptome resources (Robinson et al, 2012;Sahu et al, 2013) in this species. However, whole genome sequence of rohu carp is still lacking.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…A 17% higher average growth rate per generation was achieved after four generations of selection (Das Mahapatra et al, 2006). Our previous studies have also reported DNA markers such as SSRs (Das et al, 2005;Patel et al, 2009;Sahu et al, 2012), SSR and SNP -based linkage maps (Robinson et al, 2014;Sahoo et al, 2015) and transcriptome resources (Robinson et al, 2012;Sahu et al, 2013) in this species. However, whole genome sequence of rohu carp is still lacking.…”
Section: Introductionmentioning
confidence: 70%
“…Further, the Illumina PE reads were mapped to assembly sequences for analyzing depth distribution for every base in the genome. The accuracy of the assembly was evaluated by anchoring the scaffolds onto published SNP and microsatellite marker maps for rohu (Robinson et al, 2014;Sahoo et al, 2015). For this, SNPs and microsatellite markers of rohu were used as queries against rohu scaffolds by Blastn module as implemented in the program CLC Bio workbench version 7.0.4, with the following parameters: e-value 1e-10, word size 10, match 2, mismatch −3 and % identity 90%.…”
Section: De Novo Genome Assembly and Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Maximum number of bases interrupting between two SSRs in a compound microsatellite was taken as 100. For the analysis of microsatellite polymorphism, DNA from 3 parents belonging to two linkage mapping panels of rohu [ 33 ] and 2 individuals (one each) from resistant and susceptible lines of rohu against aeromoniasis [ 5 ] was used to test the gene loci for diversity. Number of alleles, observed heterozygosity (HO), expected heterozygosity (HE) and polymorphic information content (PIC) were estimated using CERVUS software ver 3.0 ( http://www.fieldgenetics.com/pages/home.jsp ).…”
Section: Methodsmentioning
confidence: 99%
“…Certain attributes like high allelic diversity, codominant inheritance, high abundance and genomewide distribution have made microsatellite markers a versatile genetic marker system. In our previous studies, 554 SSR markers were developed, the first generation linkage map constructed for L. rohita (Das et al 2005;Patel et al 2009;Sahoo et al 2015), and were extensively tested for cross-species transferability in Labeo bata (Patel et al 2010). Preliminary studies of microsatellite marker-based parentage assignment on rohu resulted in poor matching rates (Meher et al 2014).…”
mentioning
confidence: 99%